An alternative model of international migration: Endogenous two sided borders and optimal legal systems - Inaam Chaabane; Damien Gaumont (IZA Journal of Migration, 2015)
In a 2-country and 3-period OLG model with education, we study the impact on international migration of the two sided characteristics of borders. Individuals must first "leave" their home country before "entering" the destination country. Indeed, each social planner chooses the static welfare optimal level of education, consumption, labor and capital. A unique migration flow is compatible with the market steady-state equilibrium and the maximizing social welfare solution. Difference in education generates differences in steady-state capital per capita. Consequently, both price differentials and incentives for illegal migration exist. Application to real world cases is provided.
Keywords: K37; D91; F22; 330; International migration; Overlapping generations models; Immigration law and legal systems